Nature and conditions of psychotherapist's thinking - Scherbina, L. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The analysis of the essence and conditions of development of the therapist thinking was done. The philosophical and psychological approaches to the definition of the category of development were considered. Results of modern domestic and foreign research of thinking and views on specifics, goals and tasks of professional activity of therapist were attracted.
Keywords: development of the therapist thinking; post-formal-operational approach; dialectical thinking